KUALITAS PELAYANAN PUBLIK MELALUI PENERAPAN ELECTRONIC TRAFFIC LAW ENFORCEMENT (ETLE) DI KANTOR DIREKTORAT LALU LINTAS KOTA PALU - Nia, Arnia; Mustainah; Sri Astuti, Agusta (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
This study aims to determine the Quality of Public Services Related to the Implementation of Electronic Traffic Law Enforcement (ETLE) at the Office of the Traffic Directorate of Palu City. The research method used is Descriptive Qualitative, which provides an overview of the phenomenon or focus of the problem being studied that occurs at the research location according to existing facts. The data collection techniques used are observation, in-depth informant interviews and documentation to collect the required data in the form of primary data and secondary data. While the informants in this study amounted to 7 people, namely 4 people from the Traffic Directorate and 3 people from the violating community. The theory used in this research is Gespersz's theory in Hardyansyah (2011: 51). where there are ten indicators used in Service Quality Through the Application of Electronic Traffic Law Enforcement to the Office of the Directorate of Traffic in Palu City. The ten indicators are timeliness, service accuracy, friendliness and friendliness, responsibility, completeness, convenience, variety, personal service, comfort, attributes. Based on the results of the study, it shows that the Quality of Public Services Through the Implementation of Electronic Traffic Law Enforcement (ETLE) at the Office of the Traffic Directorate of the Central Sulawesi Regional Police, has been running optimally on indicators of Service Accuracy, Politeness and Friendliness, Responsibility, Completeness, Personal Service, Comfort and Attributes. Meanwhile, the indicators of Timeliness, Ease and Variety have not run optimally. This can be seen from the Timeliness of providing services having to wait a few minutes due to network problems while the Ease indicator in providing services is the ETLE service flow which is complicated to follow and the variation indicator in providing services. All forms of this problem need improvement so that in the future it can run well.